Negotiating the Narrative Themes of Traditional Ghanaian Dance Forms within the Museum Context - Awuah, E.B. (My University, 2016)
As facilities for preserving tangible heritage, museums and galleries have partially opened up to the idea of merging intangible cultural heritage, such as dance, storytelling, and music, with their tangible collections. As lived heritage that serves as an emotional, spiritual and physical reflection of the people that created it, traditional dance can add to the socio-cultural understanding of tangible artefacts. This article discusses the possibilities and problems of using traditional dances from Ghana within the nouvelle musŽologie context (de Varine-Bohan, 1976), touching on the functionality of museum spaces, ownership, and interpretability of artefacts in relationship to the embedded narratives and contextual themes of the dances. It considers the practical implications of the thematic synergy between dance and artefacts and explores the potential uses of Ôneo-traditionalÕ dance genres in GhanaÕs museums.
Keywords: Ghana; dance in museums; nouvelle musŽologie; neo-traditional dance